Ubiquitination dynamics in the early‐branching eukaryote Giardia intestinalis. Issue 3 (23rd April 2013) - Niño, Carlos A.; Chaparro, Jenny; Soffientini, Paolo; Polo, Simona; Wasserman, Moises
Abstract Ubiquitination is a highly dynamic and versatile posttranslational modification that regulates protein function, stability, and interactions. To investigate the roles of ubiquitination in a primitive eukaryotic lineage, we utilized the early‐branching eukaryote Giardia intestinalis. Using a combination of biochemical, immunofluorescence‐based, and proteomics approaches, we assessed the ubiquitination status during the process of differentiation in Giardia. We observed that different types of ubiquitin modifications present specific cellular and temporal distribution throughout the Giardia life cycle from trophozoites to cyst maturation. Ubiquitin signal was detected in the wall of mature cysts, and enzymes implicated in cyst wall biogenesis were identified as substrates for ubiquitination. Interestingly, inhibition of proteasome activity did not affect trophozoite replication and differentiation, while it caused a decrease in cyst viability, arguing for proteasome involvement in cyst wall maturation. Using a proteomics approach, we identified around 200 high‐confidence ubiquitinated candidates that vary their ubiquitination status during differentiation. Our results indicate that ubiquitination is critical for several cellular processes in this primitive eukaryote.